2009
DOI: 10.1007/s12010-009-8628-6
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–Alginate Microcapsules for Oral Delivery of Egg Yolk Immunoglobulin (IgY): Effects of Chitosan Concentration

Abstract: In our previous study, chitosan-alginate microcapsules were developed to protect egg yolk immunoglobulin (IgY) from gastric inactivation. The present study was undertaken to determine the effect of chitosan concentration (0-0.8%; w/v) on various properties of the microcapsules in order to produce the optimum chitosan-alginate microcapsules for use in the oral delivery of IgY. The properties investigated included microcapsule morphology, loading capacity for IgY (expressed as the IgY loading percentage, w/w, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The principle is to evenly disperse the core material in the wall material solution and then add another substance or solvent to condense the wall material mixture and form microcapsules around the core material [110]. Li et al successfully used sodium alginate and chitosan to microencapsulate yolk immunoglobulin and found that sodium alginate/chitosan microcapsules can effectively protect yolk immunoglobulin from the killing effect of gastric juice [111]. The phase separation method is a very effective microencapsulation technology with a relatively simple process, and the embedding rate is 85%~90%.…”
Section: Bottom-up Processing Technologymentioning
confidence: 99%
“…The principle is to evenly disperse the core material in the wall material solution and then add another substance or solvent to condense the wall material mixture and form microcapsules around the core material [110]. Li et al successfully used sodium alginate and chitosan to microencapsulate yolk immunoglobulin and found that sodium alginate/chitosan microcapsules can effectively protect yolk immunoglobulin from the killing effect of gastric juice [111]. The phase separation method is a very effective microencapsulation technology with a relatively simple process, and the embedding rate is 85%~90%.…”
Section: Bottom-up Processing Technologymentioning
confidence: 99%
“…The macroencapsulation of IgY using enteric-coated gelatin capsules has also been examined and was found to significantly improve antibody stability (Akita & Nakai 2000). The use of a pH-sensitive methacrylic acid copolymer (Kovacs-Nolan & Mine 2005), chitosan-alginate microcapsules (Li et al 2007(Li et al , 2009a, and whey protein-based microcapsules (Cho et al 2005) have also been shown to increase IgY stability to gastric conditions, both in vitro and in vivo. Recently, Xun et al (2010) described the use of the cytoprotective agent sucralfate and found that it could improve IgY resistance to low pH and pepsin treatment, as well as enhance storage stability, in a dose-dependent manner.…”
Section: Molecular Properties Of Igymentioning
confidence: 99%
“…In a more recent report, the same team showed that an initial chitosan solution of 0.2% (w/v) resulted in maximal microcapsules production efficiency, IgY protection against SGF for at least 2 h, and effective release of IgY in SIF (Li et al, 2009c). The encapsulation of IgY by chitosan-alginate significantly improved the stability of IgY compared with encapsulation by alginate (69% of IgY activity vs. 44%).…”
Section: Proteinsmentioning
confidence: 96%
“…This complexation reduces the porosity of alginate particles and prevents the fast release of formulated drugs (Murata et al, 1993;Polk et al, 1994;Sezer and Akbuga, 1999). In this case, the calcium ions, because of their low molecular weight, diffuse more rapidly than chitosan into the alginate core to form a gel core (Li et al, 2009c). The first procedure is a one-step method whereby the alginate solution is dropped into a chitosan solution containing calcium chloride.…”
Section: Formulation Of Active Agents With Chitosan-alginate Pecmentioning
confidence: 99%